Acute flaccid myelitis: cause, diagnosis, and management. Issue 10271 (23rd January 2021) - Murphy, Olwen C; Messacar, Kevin; Benson, Leslie; Bove, Riley; Carpenter, Jessica L; Crawford, Thomas; Dean, Janet; DeBiasi, Roberta; Desai, Jay; Elrick, Matthew J; Farias-Moeller, Raquel; Gombolay, Grace Y; et al.
Summary: Acute flaccid myelitis (AFM) is a disabling, polio-like illness mainly affecting children. Outbreaks of AFM have occurred across multiple global regions since 2012, and the disease appears to be caused by non-polio enterovirus infection, posing a major public health challenge. The clinical presentation of flaccid and often profound muscle weakness (which can invoke respiratory failure and other critical complications) can mimic several other acute neurological illnesses. There is no single sensitive and specific test for AFM, and the diagnosis relies on identification of several important clinical, neuroimaging, and cerebrospinal fluid characteristics. Following the acute phase of AFM, patients typically have substantial residual disability and unique long-term rehabilitation needs. In this Review we describe the epidemiology, clinical features, course, and outcomes of AFM to help to guide diagnosis, management, and rehabilitation. Future research directions include further studies evaluating host and pathogen factors, including investigations into genetic, viral, and immunological features of affected patients, host–virus interactions, and investigations of targeted therapeutic approaches to improve the long-term outcomes in this population.